Linguistic Politeness in Public Virtual Communication - Z Zainurrahman; Mintesya Kofau (Jurnal Langua, 2020)
Linguistic politeness has become an interesting discussion among linguists. Many thoughts and concepts have been constructed in order to explain the phenomenon of linguistic politeness. In fact, there are controversies among these concepts or models. However, currently available models of linguistic politeness tend to focus on direct (face-to-face) communication. What about public virtual communication? This article aims to discuss linguistic politeness in public virtual communication where important elements in the models of linguistic politeness that exist today can be tested. By trawling the comments of several videos on YouTube, we found that positive politeness is the polarity of politeness that is mostly used. Meanwhile, negative politeness is still outnumbered even with the bald strategy. Using descriptive analysis, we express the opinion that positive politeness is no longer a communication strategy in public virtual communication but a norm. Linguistic politeness is only really identified in negative politeness because even though they don't know each other and therefore social distance cannot be measured, they still use negative politeness to maintain their self-esteem and the people they communicate with. In this regard, it is very clear that linguistic courtesy in public virtual communication is a "face-saving" act, especially negative politeness.